Laser-induced breakdown spectroscopy determination of K in biochar-based fertilizers in the presence of easily ionizable element - de Morais, Carla Pereira [UNESP]; Barros, Ariane Isis [UNESP]; Bechlin, Marcos André [UNESP]; Silva, Tiago Varão [UNESP]; Júnior, Dário Santos; Senesi, Giorgio Saverio; Crespi, Marisa Spirandeli [UNESP]; Ribeiro, Clóvis Augusto [UNESP]; Gomes Neto, José Anchieta [UNESP]; Ferreira, Edilene Cristina [UNESP] (Elsevier, 2018)
Laser-induced breakdown spectroscopy is an optical emission technique quite suitable for the analysis of recalcitrant materials as it eliminates complex procedures of sample preparation. However, for some simple LIBS instrumentation the detection limits are still higher compared to those of consolidated spectroscopic techniques. The aim of the present work was to develop a method for the determination of K in new biochar-based fertilizer samples using a simple single pulse LIBS arrangement. Due to the low K detectability, which made impossible to obtain calibration curves, an exploratory qualitative study was performed aiming to evaluate the influence of the addition of easily ionizable elements (EIE) on the sensitivity. To this aim different salts containing EIE (K, Li and Na) and other cations (Cu and Mg) have been evaluated. Results obtained showed that salts containing EIE cations increased the spectral emission signals of some elements in samples previously submitted to charring. In particular, the strategy of using Li+ was applied to the determination of K in biochar-based fertilizers. The addition of Li+ allowed to develop an analytical method for K determination featuring a linear dynamic range from 0.8% to 21.56% K, and limits of detection and quantification of 0.2% and 0.8%, respectively.
Keywords: Biochar-based fertilizers; Detection improvement; Easily ionizable elements; K; LIBS